The Role of Morphological Information in Processing Pseudo-words in Italian L2 Learners: It’s a Matter of Experience - Simona Amenta; Francesca Foppolo; Linda Badan (Journal of Cognition)
The productive use of morphological information is considered one of the possible ways in which speakers of a language understand and learn unknown words. In the present study we investigate if, and how, also adult L2 learners exploit morphological information to process unknown words by analyzing the impact of language proficiency in the processing of novel derivations. Italian L2 learners, divided into three proficiency groups, participated in a lexical decision where pseudo-words could embed existing stems (e.g., sockle), suffixes (e.g., hettable), or both (novel derivations, e.g., quickify). Participants with low proficiency exhibited reduced accuracy and longer reaction times when presented with pseudo-words embedding a stem compared to those embedding a suffix. Conversely, participants with high proficiency demonstrated comparable accuracy in rejecting pseudo-words with real stems or real suffixes but required more time to reject pseudo-words embedding a suffix. In the case of novel derivations, accuracy (i.e., correct rejection) decreased and reaction time increased for all proficiency groups. Our results show that L2 learners exploit morphological information to process novel words. Most importantly, the ability to extract and exploit morphological information is linked to language proficiency.